2022
DOI: 10.1007/s42000-022-00387-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between lower plasma adiponectin levels and higher liver stiffness in type 2 diabetic individuals with nonalcoholic fatty liver disease: an observational cross-sectional study

Abstract: Purpose Little is known about the association between plasma adiponectin levels and nonalcoholic fatty liver disease (NAFLD) in patients with type 2 diabetes mellitus (T2DM). We examined whether there is an association between lower plasma adiponectin levels and the presence/severity of NAFLD in people with T2DM. Methods We cross-sectionally recruited 79 men with non-insulin-treated T2DM and no known liver diseases, who had consecutively attended our diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Mikolasevic et al 26 found that HOMA-IR was independently associated with hepatic steatosis, but not with moderate and advanced LF in T2DM patients with NAFLD. Mantovani et al 55 conducted a cross-sectional study on T2DM patients who were not treated with insulin. The diagnosis of NAFLD is based on abdominal color ultrasound and liver hardness measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Mikolasevic et al 26 found that HOMA-IR was independently associated with hepatic steatosis, but not with moderate and advanced LF in T2DM patients with NAFLD. Mantovani et al 55 conducted a cross-sectional study on T2DM patients who were not treated with insulin. The diagnosis of NAFLD is based on abdominal color ultrasound and liver hardness measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the Agile 3+ score has been demonstrated to perform satisfactorily in the noninvasive One benefit of this approach is identifying patients who would benefit the most from preventive strategies focused on managing comorbidities and weight loss. [18,29,30] This can help prevent the progression of MASLD to advanced liver disease. Additionally, accurately excluding patients without advanced fibrosis is crucial as it allows a better allocation of health and economic resources in tertiary care centers.…”
Section: Discussionmentioning
confidence: 99%
“…46 Adiponectin is specifically expressed in adipose tissue and its serum level is inversely associated with the risk of type 2 diabetes and the presence of fibrosis in NAFLD. 47,48 Adiponectin inhibits progression to steatosis/steatohepatitis 49 A recent study from a single referral hospital in Japan reported that 105 out of 535 (20%) exhibited at least partial SH-HCC feature and more prevalent SH-HCC (40%) was observed among patients with NASH compared with those with other etiologies. 53 Other histological studies from the United States and Brazil showed that 71% and 70% of HCC from NAFLD were diagnosed as SH-HCC, respectively.…”
Section: Fib Ros Is -Independenthepat O C a Rci Nog Ene S Is From Nafldmentioning
confidence: 99%
“…For instance, adipokines released from adipose tissue can influence hepatocarcinogenesis from NAFLD 46 . Adiponectin is specifically expressed in adipose tissue and its serum level is inversely associated with the risk of type 2 diabetes and the presence of fibrosis in NAFLD 47,48 . Adiponectin inhibits progression to steatosis/steatohepatitis 49 and protects against liver hepatocarcinogenesis by inducing apoptosis via increased phosphorylation of JNK and activation of caspase 3 50 .…”
Section: Fibrosis‐independent Hepatocarcinogenesis From Nafldmentioning
confidence: 99%